Implementation of Multicultural Education in an effort to Develop the Tasamuh Attitude of Santri at Islamic Boarding Schools in Central Lampung Regency - Alwi Hasan; Mispani Mispani; Siti Roudhotul Jannah (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2022)
Islamic boarding schools in Central Lampung Regency have students consisting of various ethnic groups, such as Javanese, Sundanese, Lampung, Padang , and Palembang. This reality can cause problems if the educational process is carried out in a discriminatory way against one particular tribe. The purpose of this study was to determine the materials and methods of education as well as the implementation of multicultural education in an effort to develop the tasamuh attitude of students in Islamic boarding schools in Central Lampung Regency. This research is a qualitative field research (field research) conducted in Islamic boarding schools in Central Lampung. Based on the results of the study, it can be concluded that multicultural education at the Walisongo, Roudhotusholihin, and Al-Hidayah Islamic Boarding Schools is carried out in the form of placing students from different ethnic, cultural, and economic backgrounds in the same dormitory. These conditions allow students to understand cultural and linguistic differences, and encourage a sense of togetherness and acceptance of other students. Multicultural-based subject matter at the Walisongo, Roudhotusholihin and Al-Hidayah Islamic Boarding Schools can be seen from the material on ahlussunnah wal jama'ah (Aswaja), which emphasizes the attitude of tawasuth (moderate), i`tidal (proportionate), tasamuh (tolerant), and tawazun (balanced). Social interactions at the Islamic boarding schools of Walisongo, Roudhotusholihin and Al-Hidayah describe a pluralistic community, which is based on the values ​​of morality.